Ionomer, preparation method of ionomer, and catalyst layer slurry and membrane electrode for hydrogen production by electrolysis of water
By developing ionomers that can interact with the catalyst, the stability and uniformity of the catalyst ink are improved, and the problem of poor catalyst uniformity and stability in the membrane electrode is solved, and efficient hydrogen production performance and long-life membranes are achieved through the development of ionomers that can interact with the catalyst, which is a good choice for the catalyst in the membrane electrode. electrode.
Patent Information
- Application Number
- CN202411612761.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-12
AI Technical Summary
In the existing water electrolysis hydrogen production technology, the poor uniformity and stability of transition metal catalysts such as NiFe in membrane electrodes lead to a degradation of the catalytic layer performance, especially poor ion conduction and gas transmission at high current density, catalyst activity and use Lifespan is limited.
Develop an ionomer that can interact with the catalyst, improve the stability and uniformity of the catalyst ink by introducing specific groups into its structure, and prepare the catalytic layer slurry by ultrasonic dispersion and stirring to form high yield stress and The protective layer inhibits the thermodynamic instability and aggregate formation of the catalyst.
The stable dispersion of the catalyst slurry and the construction of a high-performance catalytic layer are achieved, and the current density and service life of hydrogen production by electrolyzing water are improved. The thermodynamic stability and electrochemical activity of the catalyst are significantly improved. The membrane electrode operates stably under high current density. 1400 hours.
Smart Images

Figure CN119264353A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by water electrolysis, and in particular to an ionomer, a preparation method thereof, and a catalytic layer slurry and a membrane electrode for hydrogen production by water electrolysis. Background Art
[0002] Water electrolysis technology driven by renewable energy is considered to be the most promising technology for large-scale and sustainable production of "green hydrogen". Precious metals (such as platinum Pt and iridium Ir) are the most advanced catalysts in electrolysis technology, but their high cost and scarcity severely limit the large-scale commercialization of electrolysis technology. The emerging alkaline membrane water electrolysis hydrogen production combines the advantages of low cost of alkaline water electrolysis and high efficiency of proton exchange membrane water electrolysis. It has the advantages of allowing the use of non-precious metal catalysts and fast reaction kinetics in alkaline media. It is considered to be the preferred green hydrogen production technology in the future. Transition metal (oxy) hydroxides represented by nickel iron (abbreviated as NiFe) are commonly used non-precious metal catalysts with great commercial prospects in alkaline membrane water electrolysis hydrogen production due to their high electrochemical activity, high abundance and cost advantages.
[0003] Although transition metal catalysts (such as NiFe) have been observed to have significant catalytic activity on rotating disk electrodes, there is a significant performance gap after they are prepared into membrane electrodes. This is mainly due to the poor uniformity of the catalyst ink dispersion and the poor thermodynamic stability of the transition metal, which leads to poor uniformity and stability of the catalyst layer. The membrane electrode for hydrogen production by electrolysis of water is mainly composed of a proton exchange membrane and a catalyst layer. The catalyst layer is usually composed of a catalyst and an ionomer. The ionomer is an ionized polymer material that can play a role in bonding the catalyst and conducting ions in the catalyst layer. The catalyst layer is the place for electrochemical reactions. The processes such as ion conduction, electron transfer and gas transport in the electrochemical reaction are intertwined in the catalyst layer, competing for a narrow space, greatly affecting the activity and utilization of the catalyst. Especially for water electrolyzers with high electrolysis efficiency, at high current density, the ion accessibility caused by the uneven distribution of ionomers, and the local transmission resistance of the gas through the ionomer film or ionomer aggregates, etc., lead to more serious problems of poor ion conduction and gas transmission in the catalyst layer. Therefore, some problems existing in the catalyst layer are closely related to the performance of the ionomer. In addition, taking NiFe catalyst as an example, its own thermodynamic instability causes iron dissolution and loss during operation, thereby reducing the catalyst activity and stability, which is another key factor restricting the performance and service life of the electrolyzer.
[0004] The uniform and stable construction of the catalyst layer is determined by the interaction between the ionomer and the catalyst, and is mainly affected by the dispersion and deposition process of the catalyst slurry. NiFe catalyst ink has the property of rapid precipitation due to its high density, and the large agglomerates formed are the starting point of defect crack structure. During the spraying and drying process, cracks are easily formed due to the imbalance of capillary forces between particles. Specifically, low-quality catalyst inks are mixed with large and uneven agglomerates, which lead to shear-induced particle migration and agglomeration during the deposition process. Subsequently, according to the Marangoni effect, during the drying process, the difference in surface tension gradients caused by different agglomerate sizes accelerates the formation of pore defects and mechanical damage in the catalyst layer. Therefore, the quality of catalyst inks configured by NiFe, especially the stability, is an important factor affecting the performance of membrane electrodes, which is a technical obstacle that cannot be ignored for large-scale membrane electrode production.
[0005] The addition of suitable ionomers can alleviate the formation of large catalyst aggregates to a certain extent. Ionomers rely on the van der Waals force between the polymer main chain and the catalyst to adsorb around the catalyst to form a catalyst coating. The electrostatic repulsion between the charged ionomers and the steric hindrance of the polymer inhibit the further aggregation of the catalyst coating, thereby forming a stably dispersed catalyst slurry. The network formed by the interconnection of ionomers between the catalysts gives the catalyst slurry a high yield stress, making it less likely to settle. However, this van der Waals force is very weak, making it difficult to prepare a catalyst slurry that is evenly dispersed and more stable.
[0006] In addition, most NiFe catalysts are subject to severe lattice distortion of NiO6 at high oxidation potentials, causing Fe to change from low valence to high valence. Metal elements in high valence states are extremely unstable, which can easily cause the breakage of metal-oxygen bonds and lead to the dissolution of Fe. The dissolved Fe will be randomly redeposited on the surface or doped in the main lattice under oxygen evolution conditions. This dynamic dissolution and redeposition process leads to poor iron segregation, which in turn leads to the gradual deactivation of the catalyst and the decrease in the performance and stability of the device (Nat. Catal. 2020, 3, 743-753.). The existing ionomer cortex cannot act as a protective layer to prevent this process. Therefore, how to develop ionomers that can interact with catalysts is of great significance to improving electrolytic performance and service life. Summary of the invention
[0007] In view of this, the present invention aims to provide an ionomer that can interact with a catalyst, a preparation method thereof, and a catalyst layer slurry and a membrane electrode for electrolysis of water to produce hydrogen. The ionomer described in the present invention can specifically act on transition metal catalysts, improve the stability of the catalyst and its slurry, and inhibit the generation of cracks during the spraying and drying of the catalyst slurry. However, there is no report on the technology of introducing groups that interact with catalysts into the preparation of ionomers to improve the stability of catalyst ink, the uniformity of the catalyst layer, and the stability of the catalyst.
[0008] The present invention provides an ionomer comprising a repeating unit of the structure shown in Formula 1:
[0009]
[0010] In Formula 1, Ar is a group represented by Formula a or Formula b, Q is a group represented by Formula c or Formula d, and R is a substituted or unsubstituted porphyrin or phthalocyanine group;
[0011]
[0012] Wherein, 0≤x≤10, 0≤y≤10; R0~R5 are independently selected from C1~C10 chain alkyl groups; t is selected from an integer between 0 and 3.
[0013] In an embodiment of the present invention, R is a group represented by formula e or formula f, wherein R' is selected from one or more of hydrogen, amino and phenylamino;
[0014]
[0015] The present invention provides a method for preparing the above-mentioned ionomer, comprising the following steps:
[0016] The polymer having the repeating unit of the structure of formula 2 and the quaternized monomer are reacted to obtain the ionomer shown in formula 1;
[0017]
[0018] Wherein, X is halogen or alkyl halogen; and the quaternary ammonium monomer is a fatty amine substituted with a chain alkyl group.
[0019] In a preferred embodiment of the present invention, the polymer having the repeating unit of the structure of formula 2 is prepared as follows:
[0020] A conjugated aromatic monomer containing a reactive site, an optional comonomer, and a ketone monomer are subjected to a condensation reaction to obtain an initial polymer;
[0021] The initial polymer is reacted with a functional monomer to obtain a polymer having a repeating unit as shown in Formula 2;
[0022] The conjugated aromatic monomer containing a reactive site is 9,9-bis(6-bromohexyl)-9H-fluorene; the comonomer is selected from one of biphenyl, p-terphenyl, m-terphenyl, fluorene and dibromoalkylfluorene; the ketone monomer is selected from one of 1,1,1-trifluoroacetone, 2,2,2-trifluoroacetophenone, 2,2,2,4'-tetrafluoroacetophenone and perfluoroacetophenone;
[0023] The functional monomer is selected from one of 5-(4-aminophenyl)-10,15,20-tri(phenyl)porphyrin, 5,15-(aminophenyl)-10,20-phenylporphyrin and monoaminophthalocyanine.
[0024] Preferably, the polycondensation reaction is carried out in a first solvent under the action of a first catalyst, wherein the first catalyst is trifluoroacetic acid and / or trifluoromethanesulfonic acid; the temperature of the polycondensation reaction is 0 to 20° C., and the time is 1 to 48 hours.
[0025] Preferably, the Menxiujin reaction is carried out in a second solvent under the action of a second catalyst, the second catalyst is potassium carbonate and / or cesium carbonate; the molar ratio of the initial polymer to the functional monomer is 1:0.1-0.5, and the temperature of the Menxiujin reaction is 80-100°C.
[0026] Preferably, the molar ratio of the polymer having the repeating unit of the structure of formula 2 to the quaternized monomer is 0.5 to 1:1, and the reaction temperature of the two is 30 to 80° C. and the reaction time is 12 to 48 hours.
[0027] Compared with the prior art, the ionomer provided by the present invention includes a repeating unit structure as shown in Formula 1, wherein R is a substituted or unsubstituted porphyrin or phthalocyanine group, and the quaternary ammonium ionized group Q + All of them are side groups on the aromatic macromolecule Ar. In the present invention, the ionomer having the repeating unit shown in Formula 1 has a specific electrostatic interaction and coordination effect with the transition metal atoms on the transition metal catalyst, which can achieve uniform distribution of the ionomer around the catalyst and inhibit the formation of catalyst aggregates, thereby improving the stability and rheology of the catalyst slurry, and then obtaining a membrane electrode catalyst layer with better performance. At the same time, the groups on the ionomer that have a special effect on the catalyst serve as a protective layer, which can be used to enhance the bond energy of Fe-O bonds, etc., slow down the dissolution of transition metals such as Fe, and improve the thermodynamic stability of the catalyst, which is conducive to application.
[0028] The present invention provides a catalytic layer slurry for producing hydrogen by electrolyzing water, comprising a binder, a transition metal catalyst and an organic solvent, wherein the binder is the ionomer described above.
[0029] In an embodiment of the present invention, the transition metal catalyst contains transition metal atoms that interact with the ionomer, such as Fe, Ni, Co, Zn, Mn, etc.; the organic solvent is selected from any one or a combination of at least two of isopropanol, methanol, ethanol, n-propanol and water.
[0030] In an embodiment of the present invention, the catalytic layer slurry is obtained from the ionomer, catalyst and solvent by ultrasonic dispersion, stirring or ball milling.
[0031] The present invention provides a membrane electrode, comprising a catalyst layer, wherein the catalyst layer is prepared by ultrasonic spraying and / or slit coating of the catalyst layer slurry.
[0032] Furthermore, the present invention provides application of the membrane electrode in hydrogen production by alkaline membrane water electrolysis.
[0033] Based on the ionomer material described above, the membrane electrolysis was assembled in an alkaline membrane water electrolysis hydrogen production device and operated under certain conditions. The experiment showed that at 1.8V, the maximum current density of the water electrolysis hydrogen production reached 4.06A / cm, and the electrolysis system was ≥1.0A / cm 2 It ran stably for 1400 hours at a high current density, which improved the electrolytic performance and service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 The ionomer prepared in Example 1 of the present invention 1 H NMR spectra;
[0036] Figure 2 The ionomer prepared in Comparative Example 1 of the present invention 1 H NMR spectra;
[0037] Figure 3 The ionomer prepared in Example 2 of the present invention 1 H NMR spectra;
[0038] Figure 4 The mechanical properties of the ionomers prepared in Example 1 and Comparative Example 1 after film formation;
[0039] Figure 5 The thermal stability of the ionomers prepared in Example 1 and Comparative Example 1 after film formation;
[0040] Figure 6 A microscopic morphology image of a catalyst ink prepared by preparing an ionomer according to Example 1 of the present invention;
[0041] Figure 7 This is a diagram of the size of the agglomerates of the catalyst ink prepared in Example 3 of the present invention;
[0042] Figure 8 The sedimentation stability of the catalyst ink prepared in Example 3 of the present invention;
[0043] Fig. 9 The rheological properties of the catalyst ink prepared in Example 3 of the present invention;
[0044] Fig.10 The large-area catalytic layer prepared in Example 4 of the present invention;
[0045] Fig.11 This is a microscopic morphology of a large-area catalytic layer prepared in Example 4 of the present invention;
[0046] Fig.12 A gas adsorption and desorption diagram of a large-area catalyst layer prepared in Example 4 of the present invention;
[0047] Fig.13 The electrochemically active area of the large-area catalyst layer prepared in Example 4 of the present invention;
[0048] Fig.14 This is a stability test diagram of a large-area catalytic layer prepared in Example 4 of the present invention;
[0049] Fig.15 This is a diagram showing the element content after stability testing of the large-area catalyst layer prepared in Example 4 of the present invention;
[0050] Fig.16 This is a performance diagram of hydrogen production from electrolysis of water of a large-area catalytic layer prepared in Example 4 of the present invention;
[0051] Fig.17 This is a durability diagram of hydrogen production by electrolysis of water using a large-area catalytic layer prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0052] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the technical scheme of the present invention is now described in detail below in conjunction with specific embodiments. The described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments.
[0053] The present invention provides an ionomer comprising a repeating unit of the structure shown in Formula 1:
[0054]
[0055] In Formula 1, Ar is a group represented by Formula a or Formula b; in Formula a, 0≤x≤10, 0≤y≤10;
[0056]
[0057] Q is a group represented by formula c or formula d, wherein R1 to R5 are independently selected from a C1 to C10 chain alkyl group; t is selected from an integer between 0 and 3;
[0058]
[0059] R is a substituted or unsubstituted porphyrin or phthalocyanine group; R0 is selected from a C1-C10 chain alkyl group.
[0060] The ionomer including the repeating unit of the structure shown in Formula 1 may be a homopolymer or a copolymer, that is, it may include other repeating units, such as a copolymer structure including biphenyl, p-terphenyl, m-terphenyl, fluorene and dibromoalkylfluorene.
[0061] In some embodiments of the present invention, Ar has a structure of formula a, and the connecting single bonds at both ends of the main chain can be located at one or more of the ortho, meta and para positions of the benzene ring, preferably at the same position. In formula a, x and y can both be 0, preferably 1≤x≤9, 1≤y≤9, further preferably 2≤x≤7, 2≤y≤7; both are preferably the same, both 5 or both 6, as shown in the following formula:
[0062]
[0063] In other embodiments of the present invention, Ar has a structure of formula b, and the connecting single bonds at both ends of the main chain can be located at one or more of the ortho, meta and para positions of the benzene ring, preferably at the same position. Specifically, formula b includes the following structure:
[0064]
[0065] In some embodiments of the present invention, Q is a structure shown in formula c, the cation is located at the nitrogen atom, and is a chain alkyl quaternary ammonium cation structure, which can be represented as follows, t is 0, 1, 2 or 3; R1, R2 and R3 are independently selected from chain alkyl groups of C1 to C10, and can all be alkyl groups with 1 carbon atom, that is, methyl (CH3);
[0066]
[0067] In some embodiments of the present invention, Q is a structure shown in formula d, the cation is located at the nitrogen atom, and is an aliphatic cyclic quaternary ammonium cation structure, which can be represented as follows, t is 0, 1, 2 or 3, preferably 1; R4 and R5 are independently selected from C1 to C10 chain alkyl groups, and can be both methyl or both ethyl;
[0068]
[0069] In the above formulas a to d, the zigzag lines represent the positions where the groups are connected to each other. Ar described in the present invention is connected to C-CF3 (R0), and in addition to the trifluoromethyl group (CF3) connected to C, the connected R0 is a C1-C10 chain alkyl group, preferably a methyl group or an ethyl group.
[0070] In the present invention, R is a substituted or unsubstituted porphyrin or phthalocyanine group, which can interact with metal atoms Fe, Ni, Co, Zn, Mn, etc. in transition metal catalysts. The R can be independently selected according to the type of catalyst, and is preferably a group shown in formula e or formula f:
[0071]
[0072] Wherein, R' is selected from one or more of hydrogen (H), amino (NH2) and phenylamino.
[0073] The embodiment of the present invention also provides a method for preparing the ionomer, comprising the following steps:
[0074] A) subjecting a conjugated aromatic monomer containing a reactive site, an optional comonomer, and a ketone monomer to a condensation reaction in a first solvent under the action of a first catalyst to obtain an initial polymer;
[0075] B) Under the action of a second catalyst, the initial polymer and the functional monomer that interacts with the catalyst are subjected to a gate-shine gold reaction in a second solvent to obtain a polymer that interacts with the catalyst, that is, a polymer having a structural repeating unit of formula 2, wherein X is a halogen or an alkyl halogen, and the halogen is preferably bromine (Br);
[0076] C) reacting the polymer represented by the formula 2 and the quaternized monomer in a third solvent to obtain
[0077] An ionomer of a repeating unit of the structure of formula 1;
[0078]
[0079] In an embodiment of the present invention, the conjugated aromatic monomer containing a reactive site is 9,9-bis(6-bromohexyl)-9H-fluorene, and the structure is as follows; the conjugated aromatic monomer containing a reactive site can be obtained by reacting fluorene and 1,6-dibromohexane;
[0080]
[0081] Alternatively, the comonomer is selected from one of biphenyl, p-terphenyl, m-terphenyl, fluorene and dibromoalkylfluorene. Also, the ketone monomer is selected from one of 1,1,1-trifluoroacetone, 2,2,2-trifluoroacetophenone, 2,2,2,4'-tetrafluoroacetophenone and perfluoroacetophenone.
[0082] In step A), the first catalyst is preferably selected from one of trifluoroacetic acid and trifluoromethanesulfonic acid; the molar ratio of the conjugated aromatic monomer containing a reactive site to the comonomer is 1:(0-1); the molar ratio of the conjugated aromatic monomer or comonomer containing a reactive site to the ketone monomer is preferably 1:(1.05-1.2). The volume ratio of the first solvent to the first catalyst may be (0-1):1; the temperature of the polycondensation reaction is preferably 0-20°C, and the time is 1h-2d.
[0083] In step B), the monomer that interacts with the catalyst is called a functional monomer, preferably selected from 5-(4-aminophenyl)-10,15,20-tri(phenyl)porphyrin, 5,15-(aminophenyl)-10,20-phenylporphyrin and monoaminophthalocyanine. The second catalyst is preferably selected from one of potassium carbonate and cesium carbonate; the molar ratio of the initial polymer to the functional monomer is preferably 1:(0.1-0.5); the second solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-diethylformamide and dimethyl sulfoxide; the temperature of the Menxiujin reaction is preferably 80-100°C and the time is 48-60h. Among them, in order to facilitate the distinction between the catalyst and solvent in the two steps, they are marked as the first and the second, and the subsequent steps are similar. The Menxiujin reaction refers to the reaction of primary amines and halogenated hydrocarbons to form quaternary ammonium salts.
[0084] In step C), the quaternary ammonium monomer is a chain alkyl-substituted fatty amine, which may be a chain alkyl-substituted straight-chain fatty amine or alicyclic amine, such as trimethylamine; the molar ratio of the polymer of the repeating unit shown in formula 2 to the quaternary ammonium monomer is preferably (0.5-1): 1. The third solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-diethylformamide and dimethyl sulfoxide, the reaction temperature is preferably 30-80°C, more preferably 35-70°C, and the reaction time can be 12-48h.
[0085] The ionomer provided in the embodiment of the present invention or the ionomer obtained by the preparation method can be used as a binder material and applied in the technology of producing hydrogen by electrolysis of water. The ionomer can form an ionomer film layer with good performance.
[0086] The embodiment of the present invention provides a catalyst layer slurry for hydrogen production by water electrolysis, especially for hydrogen production by alkaline membrane water electrolysis, wherein the catalyst layer slurry comprises a binder, a transition metal catalyst and an organic solvent, wherein the binder is the ionomer described above; the slurry concentration is between 0.01-0.03wt%, and the mass ratio of the catalyst to the ionomer is between 5:1-3:1. The transition metal catalyst contains transition metal atoms that interact with the ionomer, such as Fe, Ni, Co, Zn, Mn, etc.; the organic solvent is selected from any one or a combination of at least two of isopropanol, methanol, ethanol, n-propanol and water.
[0087] The catalytic layer slurry is also called catalyst slurry, which can be prepared from the ionomer, catalyst and organic solvent, preferably prepared from the ionomer, catalyst and organic solvent by ultrasonic dispersion, stirring or ball milling.
[0088] The embodiment of the present invention provides a membrane electrode catalyst layer, which is prepared by ultrasonic spraying and / or slit coating of the catalyst slurry. Correspondingly, the embodiment of the present invention provides a membrane electrode, including a catalyst layer, which is prepared by ultrasonic spraying and / or slit coating of the catalyst layer slurry under heating conditions; the catalyst ink spray flow rate can be 0.05-2.0mL / min, the heating temperature is between 40-80℃, and the loading is 0.5-4.0mg / cm 2 , area 1-625cm 2 .
[0089] The embodiment of the present invention provides the application of the membrane electrode in the production of hydrogen by alkaline membrane water electrolysis, that is, the embodiment of the present invention also provides a method for producing hydrogen by alkaline membrane water electrolysis, and the water electrolysis fixture is composed of anode and cathode end plates, cathode and cathode electrode plates, cathode and cathode flow channel plates, cathode and cathode catalyst layers, and alkaline membranes. The production of hydrogen by water electrolysis is mainly carried out by the membrane electrode catalyst layer, and the electrolyte can be specifically 1M KOH, first at 60°C, 0.2A / cm 2 The electrolytic system of the embodiment of the present invention has good performance and is conducive to extending the service life.
[0090] In order to further understand the present invention, the ionomer material, preparation method and application provided by the present invention are described in detail below in conjunction with the examples, and the protection scope of the present invention is not limited by the following examples. In the examples, all raw reagents and materials can be obtained commercially, and the experimental methods without specifying specific experimental conditions are conventional methods and conditions well known in the art.
[0091]
[0092] Weigh fluorene (8.31 g, 50 mmol) and 1,6-dibromohexane (36.6 g, 150 mmol) in a 500 mL round-bottom flask, add 250 mL of 50% sodium hydroxide aqueous solution, heat to 90 ° C, react for 12 hours under a nitrogen atmosphere, and extract the product with dichloromethane and water. Purify it by column chromatography to obtain 9,9-bis(6-bromohexyl)-9H-fluorene.
[0093] Example 1
[0094] Weigh 9,9-bis(6-bromohexyl)-9H-fluorene (4.92 g, 10 mmol) and 1,1,1-trifluoroacetone (1.35 g, 12 mmol), add them into a round-bottom flask, add 15 mL of dichloromethane, add 20 mL of trifluoromethanesulfonic acid at 0°C, react for half an hour, the product precipitates in ethanol, collect the solid and dry it to obtain a crude product, dissolve the crude product in chloroform and then precipitate it in methanol to obtain an initial polymer;
[0095] The initial polymer is firstly prepared according to the following formula to obtain a polymer having a repeating unit as shown in Formula 2, and then an ionomer is obtained.
[0096] Specifically, the initial polymer (5.86 g, 10 mmol), 5-(4-aminophenyl)-10,15,20-tri(phenyl)porphyrin (0.694 g, 1.1 mmol) and potassium carbonate (0.453 g, 3.3 mmol) were weighed, dissolved in 100 mL of N,N-dimethylformamide, heated to 80 ° C, reacted under a nitrogen atmosphere for 48 hours, and then the reaction solution was cooled to room temperature. 5 mL of trimethylamine was added for quaternization, and the reaction was continued for 24 hours. The product was precipitated in diethyl ether, and the solid was collected and dried to obtain an ionomer. Figure 1 is the H NMR spectrum of the prepared ionomer.
[0097]
[0098] Comparative Example 1
[0099] In order to better highlight the advantages of introducing the catalyst interaction groups, this comparative example prepared an ionomer with the same ion exchange group content but without the catalyst interaction groups. This is the difference between the ionomer of this comparative example and Example 1.
[0100] Comparative ionomer synthesis
[0101] Weigh 9,9-bis(6-bromohexyl)-9H-fluorene (2.2 g, 4.5 mmol), fluorene (0.92 g, 5.5 mmol) and 1,1,1-trifluoroacetone (1.35 g, 12 mmol), add them into a round-bottom flask, add 8 mL of dichloromethane, add 10 mL of trifluoromethanesulfonic acid at 0°C, react for half an hour, the product precipitates in ethanol, collect the solid and dry to obtain a crude product, the crude product is dissolved in chloroform and re-precipitated in methanol to obtain a comparative polymer; weigh the comparative polymer (4.07 g, 10 mmol) and dissolve it in 80 mL of N,N-dimethylformamide, add 4 mL of trimethylamine for quaternization, react at 30°C for 24 hours, after the reaction is completed, the reaction solution is precipitated in ether, the solid is collected and dried to obtain a comparative ionomer; the above reaction process is specifically as follows, Figure 2 For the preparation of the comparative ionomer 1 H NMR spectra;
[0102]
[0103] Example 2
[0104] 1) Synthesis of initial polymer
[0105]
[0106] Weigh 9,9-bis(6-bromohexyl)-9H-fluorene (2.2 g, 4.5 mmol), fluorene (0.92 g, 5.5 mmol) and 1,1,1-trifluoroacetone (1.35 g, 12 mmol), add to a round-bottom flask, add 8 mL of dichloromethane, add 10 mL of trifluoromethanesulfonic acid at 0°C, react for half an hour, the product precipitates in ethanol, collect the solid and dry to obtain a crude product, the crude product is dissolved in chloroform and reprecipitated in methanol to obtain an initial polymer. The reaction formula of the above reaction process is shown above.
[0107] 2) Synthesis of repeating unit polymers and ionomers of formula 2 interacting with catalysts
[0108]
[0109] Weigh the initial polymer (5.53 g, 10 mmol), 5-(4-aminophenyl)-10,15,20-tri(phenyl)porphyrin (0.694 g, 1.1 mmol) and potassium carbonate (0.453 g, 3.3 mmol), dissolve in 100 mL of N,N-dimethylformamide, heat to 80 ° C, react for 48 hours under nitrogen atmosphere, and then cool the reaction solution to room temperature. Add 5 mL of trimethylamine for quaternization, continue the reaction for 24 hours, the product precipitates in ether, collect the solid and dry to obtain the ionomer. The reaction formula of the above reaction process is as shown above. Figure 3The ionomer prepared above that interacts with the catalyst 1 H NMR spectra.
[0110] Example 3
[0111] 1) Preparation of ionomer membrane
[0112] Weigh 2 g of the polyelectrolyte membrane materials of Example 1 and Comparative Example 1, add 60 mL of N-methylpyrrolidone, fully dissolve into a uniform transparent solution, apply it on a glass plate, and dry it on a hot plate at 60° C. to obtain ionomer membranes.
[0113] 2) Testing of ionomer membranes
[0114] The tensile strength of the ionomer membrane at room temperature was tested using a dynamic mechanical analyzer (model: Q800, manufacturer: TA Company, USA). Figure 4 As shown, from the stress-strain test results, it can be seen that the tensile strength of Example 1 and Comparative Example 1 is both greater than 12 MPa, and the elongation at break is greater than 10%, indicating that the two ionomers can meet the use requirements.
[0115] The thermal decomposition stability of the ionomer was tested by using a thermogravimetric analyzer (model: Q500IR, manufacturer: TA Company, USA) at a temperature of 10°C / min from room temperature to 800°C. Figure 5 As shown, from the thermogravimetric test results, it can be seen that the degradation peaks of Example 1 (QAFLN) and Comparative Example 1 (PyFLN) at around 240°C are attributed to the degradation of the quaternary ammonium group, and the degradation after 450°C is the degradation of the polymer main chain, while the highest test temperature of the ionomer material in hydrogen production by water electrolysis is 80°C, so both materials meet the application requirements.
[0116] 3) Preparation of catalyst slurry
[0117] 1 g of the ionomers prepared in Example 1 and Comparative Example 1 were respectively weighed and dissolved in 19 mL of dimethyl sulfoxide (DMSO) to prepare ionomer solutions with a mass concentration of 5%. 5 g of ionomer solution with a mass concentration of 5 w%, 1 g of NiFe catalyst (obtained by dissolving 2.595 g NiCl2 and 3.244 g FeCl3 in 10 mL deionized water and reducing them in 2 M NaBH4) and 50 g of organic solvent (isopropanol: deionized water = 4:1 volume ratio) were weighed, and the mixture was dispersed for 20 minutes using an ultrasonic probe dispersion method to obtain a catalyst slurry (which may be referred to as catalyst ink).
[0118] 4) Characterization of catalyst slurry
[0119] A transmission electron microscope (model: JEM-2011, manufacturer: JEOL Ltd.) was used to characterize the microstructure of the catalyst slurry. Figure 6 As shown, it can be seen from the test results of the transmission electron microscope that the catalyst ink of Example 1 exhibits a uniform dispersion morphology, and the presence of porphyrin groups on the ionomer interacts with the catalyst and tends to be evenly distributed around the catalyst; while the catalyst ink of Comparative Example 1 has an uneven morphology, with large bright areas, which is caused by excessive aggregation of the catalyst. The test results intuitively demonstrate the beneficial effects of the ionomer of the present invention.
[0120] The distribution of catalyst agglomerates was determined using dynamic light scattering, as Figure 7 As shown in the figure, it can be seen from the test results of the dynamic light scattering that the average aggregation size of the catalyst ink of Example 1 (QAFLN) is 687nm, while the average aggregation size of the catalyst ink of Comparative Example 1 (PyFLN) is 824nm, indicating that the ionomer used in Example 1 is uniformly distributed around the catalyst, and the aggregation behavior of the catalyst particles is suppressed by the steric hindrance effect of the ionomer. The test results are mutually confirmed with the results of the transmission electron microscope, further demonstrating the beneficial effects of the ionomer of the present invention.
[0121] The ink sedimentation stability is characterized by recording the change of ink sedimentation height over time, such as Figure 8 shown. Figure 8 Part a is the case where comparative example 1 is placed for 12 hours, and part b is the case where example 1 is placed for 108 hours. From the test results of the sedimentation stability of the ink, it can be seen that the catalyst ink of comparative example 1 has obvious sedimentation in 12 hours, while the catalyst ink of example 1 has no obvious sedimentation after 108 hours. This shows that due to the excessive agglomeration of the catalyst in comparative example 1, the large agglomerates are rapidly precipitated due to the greater gravity, while the catalyst and ionomers uniformly distributed in example 1, the catalyst particles are affected by steric hindrance, van der Waals force and double electric layer repulsion, and are not easy to aggregate into large agglomerates, so the sedimentation rate is slow, and the catalyst ink has excellent stability.
[0122] The rheological properties of the catalyst slurry were characterized by a rheometer (model: TA Discovery HR-2, manufacturer: TA Company, USA). Fig. 9 As shown (the horizontal axis is the shear rate s -1, the ordinate is shear viscosity Pa.s). It can be seen from the rheological properties of the catalyst ink that at the same shear rate, the shear viscosity of Comparative Example 1 is higher than that of Example 1, indicating that Comparative Example 1 aggregates to form more catalyst agglomerates, and when subjected to slight shear force, the agglomerates will be destroyed and the viscosity will drop rapidly. When subjected to shear force, Example 1 can reach equilibrium at a smaller shear rate, indicating that its dispersion stability is better.
[0123] Example 4
[0124] 1) Preparation of catalytic layer
[0125] The catalyst slurry was sprayed onto the polyelectrolyte membrane by ultrasonic spraying to obtain a membrane electrode. The spraying temperature was 60°C and the speed was Fig.10 As shown. Since the ionomer of Example 1 is more evenly dispersed around the catalyst, the electrostatic repulsion between the charged ionomers and the steric hindrance of the polymer are used to inhibit the catalyst coating from further agglomerating with each other, thereby forming a stably dispersed catalyst slurry, and then obtaining a catalyst layer that can be prepared on a large area.
[0126] 2) Characterization of the catalytic layer
[0127] The microstructure of the catalyst layer was characterized by atomic force microscopy (model: MultiMode V, manufacturer: Veeco, USA). Fig.11 As shown, the microscopic morphology of the catalytic layer prepared by Example 1 and Comparative Example 1 was characterized by atomic force microscopy, and it was found that the catalytic layer prepared in Example 1 showed a uniform catalytic layer morphology, and the ionomers were uniformly dispersed around the catalyst to form a skin layer of several nanometers; while in Comparative Example 1, large-area catalyst agglomeration and ionomer agglomeration were observed.
[0128] The specific surface area of the catalyst layer was tested by using a specific surface area and pore volume pore size analyzer. Fig.12 As shown. Through the carbon dioxide adsorption test on the catalytic layer, it can be seen that due to the more uniform morphology of the catalytic layer in Example 1, a higher gas adsorption amount is exhibited, indicating that the catalytic layer constructed in Example 1 has rich microporous characteristics, while in Comparative Example 1, due to the presence of larger ionomers and catalyst aggregates, the pores of the catalytic layer are blocked, and its gas adsorption amount is lower and the number of micropores is smaller.
[0129] 3) Testing of the catalytic layer
[0130] Electrochemical measurements of the samples were recorded using a standard three-electrode configuration workstation (CHI 760E). The catalyst was supported on carbon fiber paper as the working electrode, and the Hg / HgO electrode and platinum plate electrode were used as the reference electrode and counter electrode, respectively. All electrochemical measurements were performed in 1.0 M KOH electrolyte. Before the OER performance test, an activation process with chronoamperometric measurements was performed. In detail, linear sweep voltammetry (LSV) measurements were first performed on the pristine electrocatalyst to determine the appropriate potential parameters for chronoamperometric measurements of the activation process. Subsequently, the activation was performed at a scan rate of 20–100 mV·s -1 The non-Faraday cyclic voltammetry (CV) curves were collected in the SCE region. The SCE potential was calibrated to RHE:E using the Nernst equation. RHE =E Hg / HgO +0.098+0.059×pH; the electrochemically active surface area (ECSA) calculation formula is: ECSA=C dl / C s , where Cs is 1.0MKOH (0.04mF·cm -2 )'s specific capacitance.
[0131] like Fig.13 As shown, the electrochemical performance of the catalytic layer prepared by Example 1 and Comparative Example 1 was tested under a three-electrode system. From the results, it can be seen that Example 1 exhibits a higher electrochemical active area than Comparative Example 1, which indicates that due to the more uniform catalytic layer structure of Example 1, more active sites of the catalyst are exposed and the utilization rate of the catalyst is increased.
[0132] In addition, time potentiometry measurements were recorded to evaluate the electrocatalyst performance at a given constant current density of 10 mA cm -2 Long-term stability under Fig.14 The metal content of the electrolyte after the test was tested, as shown in Fig.15 shown.
[0133] The catalytic layers prepared in Example 1 and Comparative Example 1 were tested for stability under a three-electrode system. The results show that during the 100-hour test time, the voltage of Example 1 remained almost unchanged, while the voltage of Comparative Example 1 was increasing, which indicates that Example 1 is more stable. The electrolyte after the test was collected and the element content was determined using inductively coupled plasma. It was found that a higher concentration of iron was detected in Comparative Example 1, which indicates that Example 1 improves the stability of the catalytic layer by inhibiting the loss of iron.
[0134] Example 5
[0135] Hydrogen production test by water electrolysis:
[0136] Cut the anode diffusion electrode (nickel foam) and cathode diffusion electrode (carbon paper) into 2.25cm×2.25cm size. Place them on both sides of the membrane electrode prepared above, and then assemble them in the water electrolysis fixture. The alkaline membrane water electrolysis hydrogen production device is operated under the following conditions: the operating temperature is set to 80℃, the anode feed is 1MKOH, and the cathode feed is not.
[0137] The polarization curve of the above-mentioned water electrolysis hydrogen production system was tested using the Biologic battery test system. Fig.16 As shown, the operating current is then set to 1.5A / cm 2 , collect the relationship between voltage and time. The test results are as follows Fig.17 At 1.8V, the maximum current density reaches 4.06A / cm, and the electrolysis system is ≥1.0A / cm 2 The electrolytic hydrogen production performance and stability test results show that Example 1 has a more uniform catalytic morphology and the characteristics of inhibiting Fe loss of NiFe catalyst, and thus exhibits higher electrolysis performance and long-term stability.
[0138] The above examples are only used to illustrate the technical features and implementation process of the present invention, rather than to limit the technical solution of the present invention. It should be pointed out that for ordinary technicians in this field, the present invention can still be modified or replaced by equivalents, and modifications or replacements that do not deviate from the principles of the present invention are all covered by the protection of the present invention.
Claims
1. An ionomer, characterized in that: A repeating unit comprising the structure shown in Formula 1: In Formula 1, Ar is a group represented by Formula a or Formula b, Q is a group represented by Formula c or Formula d, and R is a substituted or unsubstituted porphyrin or phthalocyanine group; Wherein, 0≤x≤10, 0≤y≤10; R0~R5 are independently selected from C1~C10 chain alkyl groups; t is selected from an integer between 0 and 3.
2. The ionomer according to claim 1, characterized in that R is a group represented by formula e or formula f, wherein R' is selected from one or more of hydrogen, amino and phenylamino; 3. The method for preparing the ionomer according to claim 1, characterized in that: The following steps are involved: Reacting a polymer having a repeating unit of the structure of formula 2 with a quaternized monomer to obtain an ionomer including a repeating unit of formula 1; Wherein, X is halogen or alkyl halogen; and the quaternary ammonium monomer is a fatty amine substituted with a chain alkyl group.
4. The preparation method according to claim 3, characterized in that: The polymer having the repeating unit of the structure of formula 2 is prepared as follows: A conjugated aromatic monomer containing a reactive site, an optional comonomer and a ketone monomer are subjected to a condensation reaction to obtain an initial polymer; The initial polymer is reacted with a functional monomer to obtain a polymer having a repeating unit as shown in Formula 2; The conjugated aromatic monomer containing a reactive site is 9,9-bis(6-bromohexyl)-9H-fluorene; the comonomer is selected from one of biphenyl, p-terphenyl, m-terphenyl, fluorene and dibromoalkylfluorene; the ketone monomer is selected from one of 1,1,1-trifluoroacetone, 2,2,2-trifluoroacetophenone, 2,2,2,4'-tetrafluoroacetophenone and perfluoroacetophenone; The functional monomer is selected from one of 5-(4-aminophenyl)-10,15,20-tri(phenyl)porphyrin, 5,15-(aminophenyl)-10,20-phenylporphyrin and monoaminophthalocyanine.
5. The preparation method according to claim 4, characterized in that: The polycondensation reaction is carried out in a first solvent under the action of a first catalyst, wherein the first catalyst is trifluoroacetic acid and / or trifluoromethanesulfonic acid; the temperature of the polycondensation reaction is 0 to 20° C., and the time is 1 to 48 hours.
6. The preparation method according to claim 4, characterized in that: The Menxiujin reaction is carried out in a second solvent under the action of a second catalyst, wherein the second catalyst is potassium carbonate and / or cesium carbonate; the molar ratio of the initial polymer to the functional monomer is 1:0.1-0.5, and the temperature of the Menxiujin reaction is 80-100°C.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The molar ratio of the polymer having the repeating unit of the structure of formula 2 to the quaternary ammonium monomer is 0.5-1:1, and the reaction temperature of the two is 30-80° C. and the reaction time is 12-48 hours.
8. A catalytic layer slurry for producing hydrogen by electrolysis of water, comprising a binder and a transition metal catalyst, characterized in that: The binder is the ionomer according to any one of claims 1 to 2.
9. A membrane electrode, comprising a catalyst layer, characterized in that: The catalytic layer is prepared by ultrasonic spraying and / or slit coating of the catalytic layer slurry according to claim 8.
10. Use of the membrane electrode as claimed in claim 9 in producing hydrogen by alkaline membrane water electrolysis.
Citation Information
Patent Citations
Homogeneous catalyst and anion exchange membrane fuel cell catalyst layer
CN112563520A
Polyelectrolyte material, preparation method thereof and alkaline polyelectrolyte membrane
CN112940226A
Polyelectrolyte material and preparation method thereof and polyelectrolyte membrane
CN113621131A
Compound, polymer, electrolyte membrane, fuel cell and electrolysis apparatus
WO2024080321A1
Fluorinated polyaromatics with linear, branched or crosslinked structure for anion exchange membranes and ionomers
WO2024094894A1
Cited By
Simulation analysis method, device, equipment and medium for stretching and shearing of ionomer material
CN119889474A